Exploring The Prevalence Patterns Of Thalassemia And Quality Of Life Among Pediatric And Adolescent Patients In Sabah - Chin, Jenet Guan (2024)
Thalassemia major is a chronic disease, requires life-long blood transfusion and iron chelation therapy. Sabah has the highest amount of thalassemia in malaysia, however the true picture of the current burden of thalassemia is still not clear and studies on quality of life (qol) of thalassemia patients are also limited in sabah. This study aims to map the prevalence of thalassemia, to explore factors contributing to high prevalence of thalassemia and to determine the qol among the pediatric and adolescent patients in sabah. Study was conducted at jabatan kesihatan negeri sabah (jkns) and two hospitals in sabah from july 2018 to may 2020. Five years prevalence data was obtained from jkns. Microsoft power bi was used for mapping the prevalence. Self-administered questionnaires to 108 β-thalassemia major (β-tm) parents and in-depth, semi-structured interviews with 18 mothers having multiple β- tm children were conducted to explore the factors of having multiple β-tm children. Multiple linear regression and thematic analysis were performed. In the qol study, 115 β-tm patients aged 8 to 18 years were included. The malay version of pedsql 4.0 questionnaire was used. Multiple logistic regression was conducted to identify the factors associated with qol scores.